ANALISIS KINERJA KEUANGAN PT. â€œAâ€ INDONESIA TAHUN 2007 â€“ 2012 - Utami, Chairina; hir, Djuma (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aims to identify and analyze financial performance of PT. Â â€œAâ€ Â Indonesia inÂ 2007 - 2012 assessed by the ratio of liquidity, solvency, profitability, and activity. Â This study is a descriptive analysis research by using a quantitative approach. This studyÂ uses quantitative data as the only type of data. Based on the source, the data used in this study isÂ primary data, the data obtained directly from the PT. "A" Indonesia.Â The results of Â the company's financial performance in terms of liquidity (current ratio)Â shows there is a risk for the company in the ability Â to repay short-term liabilities. The financialÂ performance of Â the company in terms of solvency (debt to equity ratio and debt to total assetsÂ ratio) shows Â that the company has continued to decline in the ability to pay off long-termÂ liabilities from 2007 until 2010. The company's financial Â performance in term Â of profitabilityÂ (return on equity and return on assets) shows that the company started to improve and increase inÂ the rate of return on earnings through the use of capital and total assets after the acquisition. ButÂ on average, the ratio of profitability is not good. The financial performance of Â the company inÂ terms Â of Â activity (fixed asset turnover, total asset turnover, and accounts receivable turnover)Â shows that the company is getting better at using its assets effectively to increase revenue. This isÂ evidenced by the results of all Â calculations of the Â activity Â ratio that Â is Â increasing from year toÂ year.Keywords: Financial Performance, Financial Ratio Analysis, Liquidity Ratio, SolvencyÂ Ratio, Profitability Ratio, Activity Ratio.